2021
DOI: 10.35741/issn.0258-2724.56.4.7
|View full text |Cite
|
Sign up to set email alerts
|

Corporate Governance and Its Impact on Financial Performance of Commercial Banks in Ghana

Abstract: The paper examines corporate governance and its impact on the financial performance of commercial banks in Ghana. The study employs a sample of twenty commercial banks with one hundred and thirty-eight observations. Data is sourced from the audited financial statements of commercial banks through the Orbis database for seven years, from 2011 to 2017. The study employs return on assets (ROA) as a proxy for bank profitability. Also, the study uses the cost to income ratio, bank size, net interest margin, board c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 1 publication
1
3
0
Order By: Relevance
“…However, board size, non-executive directors, female directors, and board meetings do not reveal any significant relationships with both ROA and ROE panels. These findings agree with the findings of scholars such as Rose ( ), Jenson (1976 as cited by Harun (2017), Effiok et al (2012).…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…However, board size, non-executive directors, female directors, and board meetings do not reveal any significant relationships with both ROA and ROE panels. These findings agree with the findings of scholars such as Rose ( ), Jenson (1976 as cited by Harun (2017), Effiok et al (2012).…”
Section: Discussionsupporting
confidence: 91%
“…A mixed result can be also identified related to the frequency of board meetings (Karamanou et al 2005;Danoshana & Ravivathani 2013;Akpan 2015). Further, the same scenario can be also identified as related to the board ownership (Kibrysfaw Getahun 2013;Harun 2017). As existing knowledge generates puzzling results related to the areas of corporate governance and financial performance and moreover, as per the researchers' knowledge, in Sri Lankan context, few studies have been conducted related to corporate governance and financial performance with reference on listed commercial banks in Sri Lanka, it is necessary to conduct research with further investigating the relationship between corporate governance and financial performance in listed commercial banks in Sri Lanka.…”
Section: Introductionmentioning
confidence: 95%
See 2 more Smart Citations
“…Using regression analysis, results showed that there was a positive but statistically insignificant association between CEO duality and ROA and ROE". Similarly, Afriyie, Aidoo and Agboga [38] examined "corporate governance and its impact on the financial performance of commercial banks in Ghana on a sample of twenty commercial banks. For a seven -year period.…”
Section: Empirical Reviewmentioning
confidence: 99%